2005
DOI: 10.1118/1.1944288
|View full text |Cite
|
Sign up to set email alerts
|

A new simple iterative reconstruction algorithm for SPECT transmission measurement

Abstract: This paper proposes a new iterative reconstruction algorithm for transmission tomography and compares this algorithm with several other methods. The new algorithm is simple and resembles the emission ML-EM algorithm in form. Due to its simplicity, it is easy to implement and fast to compute a new update at each iteration. The algorithm also always guarantees non-negative solutions. Evaluations are performed using simulation studies and real phantom data. Comparisons with other algorithms such as convex, gradie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The microPET uses OSEM for iterative image reconstruction instead of RAMLA on the MOSAIC scanner (42). However, both algorithms have similar performance characteristics (43). To further minimize potential effects on the measurements of the T/B ratio, all images obtained from the microPET were reconstructed (as on the MOSAIC scanner) without attenuation or scatter correction, and the data analyses were performed in the same way.…”
Section: Discussionmentioning
confidence: 99%
“…The microPET uses OSEM for iterative image reconstruction instead of RAMLA on the MOSAIC scanner (42). However, both algorithms have similar performance characteristics (43). To further minimize potential effects on the measurements of the T/B ratio, all images obtained from the microPET were reconstructed (as on the MOSAIC scanner) without attenuation or scatter correction, and the data analyses were performed in the same way.…”
Section: Discussionmentioning
confidence: 99%
“…Holding x at its current value, the attenuation map μ is then updated with an ML-EM-like algorithm (Hwang and Zeng, 2005): μiitalicnew=μiitalicoldjaitalicijjaitalicijkaitalickjxkitalicnewpj where μ i is the estimated attenuation map pixel i , and the x new is the estimated image in the same iteration from equation (4). a ij is the known coefficient that represents the contribution of image pixel i to projection bin j with the old attenuation map μ.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated the importance of at tenuation correction (AC) on the quantitative accuracy of the reconstructed images for both rats and mice in emission to mography [4,5]. Conventionally, AC is performed using either a transmission (TX) or a computed tomography scan.…”
Section: Introductionmentioning
confidence: 99%